2010
DOI: 10.4049/jimmunol.0902876
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the LAT–PLC-γ1 Interaction in T Regulatory Cell Function

Abstract: The interaction between the linker for activation of T cells (LAT) with phospholipase C (PLC-γ1) is important for T cell receptor (TCR)-mediated Ca2+ signaling and MAPK activation. Knock-in mice harboring a mutation at the PLC-γ1 binding site (Y136) of LAT develop a severe lymphoproliferative syndrome. These mice have defective thymic development and selection and lack natural regulatory T cells, implicating a breakdown of both central and peripheral tolerance. To bypass this developmental defect, we developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
63
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 47 publications
9
63
0
Order By: Relevance
“…We used a qRT-PCR array for screening genes functionally associated with immune tolerance and anergy (data not shown). Notably, among other discrete changes, we observed a consistent altered expression of Lat, a gene that encodes a tyrosine phosphorylated transmembrane adaptor protein whose expression is associated with the suppressive activity of T reg cells (37,38). Recent findings showed that inhibition of LAT in mice leads to impaired immune tolerance due to diminished suppressive activity of T reg cells (37).…”
Section: Cd25mentioning
confidence: 72%
See 2 more Smart Citations
“…We used a qRT-PCR array for screening genes functionally associated with immune tolerance and anergy (data not shown). Notably, among other discrete changes, we observed a consistent altered expression of Lat, a gene that encodes a tyrosine phosphorylated transmembrane adaptor protein whose expression is associated with the suppressive activity of T reg cells (37,38). Recent findings showed that inhibition of LAT in mice leads to impaired immune tolerance due to diminished suppressive activity of T reg cells (37).…”
Section: Cd25mentioning
confidence: 72%
“…þ T reg cells (37), highlighting the importance of LAT as an inhibitory checkpoint during immune cell homeostasis. In agreement, our findings show that T reg cells from mice bearing Gal1 KD tumors express lower LAT levels and have reduced suppressive activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Akt activation was not affected by Themis1 deficiency. Together, these results show that Themis1 interacts more efficiently with Vav1-W63 variant and is required to stabilize its recruitment to the transmembrane adaptor LAT to fully promote the activation of Erk kinases that are likely necessary for the suppressive functions of Tregs (29)(30)(31).…”
Section: Vav1 Variants Impact On Themis1/vav1 Interplay and Affect Tcmentioning
confidence: 79%
“…These data are consistent with previous reports showing the critical role of the integrity of LAT signaling platform as well as Erk activation for the Treg suppressive function and the Th1/Th2 polarization (29-31, 43, 44). Indeed, the disruption of LAT/ PLC-g signalosome assembly reduces Erk and Ca 2+ activation (29,30) and despite normal Foxp3 expression, LAT-or PLCg-deficient Tregs are ineffective in controlling the proliferation of effector T cells (29)(30)(31). In addition, sustained Erk activity and calcium signaling impact on the Th1/Th2 polarization, promoting Th1 differentiation (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%